Enhanced structural stability and selective furfural hydrogenation over Ru and Si co-doped SrFeO3-δ perovskites - Bhavisha, Meloth; Joseph, Arsha P.; Gopinath, Chinnakonda S.; Balamurugan, Sarkarainadar; Venkatesha, Naragalu J.; Ganesh, Venkatachalam; Sakthivel, Ayyamperumal (New Journal of Chemistry, 2026)
Doping of SrFeO3-delta with transition and non-transition elements provides a powerful route to modulate its physicochemical properties. In this investigation, a series of ruthenium and silicon co-doped SrFeO3-delta (SrFe0.95-xRu0.05SixO3-delta) samples were prepared via the sol-gel combustion method using hexamine as fuel. The doped samples crystallized in the cubic structure with the Pm3m (221) space group. The presence of Si4+, Fe3+, Fe4+ and Ru4+ in the SrFe0.95-xRu0.05SixO3-delta sample was confirmed by XPS analysis. The presence of an EPR signal at g = 1.9393 and the temperature-programmed desorption of oxygen (TPD-O2) analyses validated the presence of oxygen vacancies. The ruthenium and silicon co-doped SrFeO3-delta effectively hydrogenates biomass-derived platform molecule furfural with 95% conversion and exhibits 88% furfuryl alcohol selectivity at 185 degrees C for 6 h under 30 bar H2 pressure. The spent ruthenium-doped SrFeO3-delta (SrFe0.95Ru0.05O3-delta) catalyst exhibited a phase transformation from the cubic perovskite structure to the brownmillerite phase with the exsolution of the metallic ruthenium species. The exsolution of metallic ruthenium can be correlated with the formation of secondary products, viz., non-selective hydrogenation leads to tetrahydrofurfuryl alcohol, furan, and methylfuran. Ruthenium and silicon co-doped perovskite oxide showed selectivity towards furfuryl alcohol with the retention of its original cubic perovskite structure. This modification of perovskite oxide with ruthenium and silicon demonstrates a highly effective strategy for engineering stable and chemo-selective catalysts for the sustainable upgrading of platform chemicals.